Aplikasi Toko Online “QMART” Berbasis Website Pada Ma’had Tahfidz Hidayatul Qur’an - Fajari, Fadhlurrahman; Fujiyanti, Linda; Agita Rindri, Yang (Jurnal Inovasi Teknologi Terapan, 2024)
This research is motivated by the implementation of the financial system at the Ma'had Tahfidz Qur'an Islamic boarding school which still uses a manual system in managing students' pocket money. This study aims to create a Qmart online store application. This application was created in order to make it easier for the guardians of students as application users to buy needs and review student finances. This research was conducted using the waterfall method, namely analysis, design, coding, testing to implementation. The skipped steps wait until the previous step is completed and must be carried out sequentially so that the process occurs linearly from the initial stage of system development to the final stage. In addition, this research uses various data collection techniques such as interviews, observations, and literature reviews. The findings show that the Qmart online store application offers a simple menu and can display the history of several transactions made. It can be concluded that the Qmart online shop application makes it easy for student guardians to meet the needs of their students and manage their finances.